The Effect of Profitability, Liquidity and Leverage on Disclosure of Islamic Social Reporting with Company Size as a Moderating Variable in Pharmaceutical Sub-Sector Companies Registered at ISSI - Amalia, Dian; Sunarsih, Sunarsih; Mohamad, Siti Nor Amira (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2023)
This study aims to examine the effect of profitability, liquidity, and leverage on the disclosure of Islamic social reporting, with firm size as a moderating variable, in the pharmaceutical sub-sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2017–2020 period. The analytical method used in this research is data regression analysis, which is then measured using the Eviews 12 test tool. Through the model feasibility test, this study uses the random effect model as the best model in the study. The results showed that before using the moderating variable, profitability had a negative influence on Islamic social reporting disclosure, and after using the moderating variable, profitability had a positive influence. Meanwhile, the liquidity variable had no effect on the disclosure of Islamic social reporting, either before or after using the moderating variable. Then the leverage variable, before using the moderating variable, had a positive effect on the disclosure of Islamic social reporting, and after using the moderating variable, it had a negative effect on the disclosure of Islamic social reporting.